VD_FINDINFO Décision / 2015 / 509 vom 25. Juni 2015 - VD Tribunal cantonal (2015)
INDEMNITÉEN GÉNÉRAL, PRÉVENU, RÉPARTITION DES FRAIS, PROCÉDÉ TÉMÉRAIRE | 426 al. 2 CPP (CH), 427 al. 2 CPP (CH), 432 CPP (CH)